A Comparative Analysis of the Financial Performance of PT XL Axiata Tbk Before and After Its Merger with PT Smartfren Telecom Tbk - Nur Hidayah K Fadhilah; Wahyu Mulyadi (The Es Accounting And Finance, 2026)
This study aims to analyze differences in the financial performance of PT XL Axiata Tbk before and after its merger with PT Smartfren Telecom Tbk. Financial performance was measured using the Current Ratio (CR), Debt-to-Equity Ratio (DER), Total Asset Turnover (TATO), and Return on Equity (ROE), representing liquidity, solvency, activity, and profitability, respectively. This study employed a quantitative descriptive-comparative approach using secondary data obtained from the companies’ official financial statements and the Indonesia Stock Exchange. The observation period covered one year before and one year after the merger, consisting of 11 paired observations for each financial ratio. Data analysis was conducted using descriptive statistics, the Kolmogorov–Smirnov normality test, and the Paired-Sample t-test. The results indicate significant differences in all financial ratios before and after the merger, with significance values below 0.05. The average CR increased from 0.5118 to 0.6209, TATO increased from 0.4564 to 0.5436, and ROE increased from 7.1091% to 8.1364%, indicating improvements in liquidity, asset utilization efficiency, and profitability. However, the average DER also increased from 1.8418 to 2.1691, reflecting greater reliance on debt financing and increased financial risk. Overall, the merger positively affected the company’s operational and financial performance, although careful management of leverage remains necessary.